The power of cat memes ! Viralité et interdiscursivité du chat remixé - Justine Simon (MediAzioni)
The article questions the notions of virality and interdisciplinarity through the semiodiscursive analysis of memes of #ChatonsMignons threads in the context of the pre-campaign of the 2022 French presidential elections. The analysis underlines how mobilized interdisciplinary references serve an argumentative dimension.